ANALISIS MISKONSEPSI PESERTA DIDIK MENGGUNAKAN TES DIAGNOSTIK PADA MATERI USAHA DAN ENERGI DI SMA SUNGAI KEHIDUPAN - Pinoh, Petrus; Sitompul, Stepanus Sahala; Habellia, Ray Cinthya (Universitas Tanjungpura, 2024)
Physics is a branch of science that investigates natural laws that are relevant to everyday life. The purpose of this research is to describe and to find out the causes of misconception in work and energy at students of SMA Sungai Kehidupan. The method of this research was qualitative descriptive method with a saturated sampling. The subject of the research was the entire population of class XA, XB and XI IPA which are 58 students. The data collection used was a diagnostic test with a multiple choice with closed reasons and interviews. The result of misconception in work and energy at students of SMA Sungai Kehidupan class XA, XB and XI IPA were a percentage of 75.86% regarding to work and energy. The profile of students